Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Masalah pada Pemecahan Konsep Matematis Siswa - Ari Tri Wijayanti; Caswita Caswita; Sugeng Sutiarso (Institut Agama Islam Negeri Curup, 2019)
This study is a research and development by following the path of Borg & Gall which includes 7 steps, namely preliminary research, planning, developing initial types / products, initial testing, major product revisions, field trials and revising operational products. The purpose of this study was to develop problem-based Student Worksheets in understanding students' mathematical concepts. The research problem was how to develop problem-based Student Worksheets on understanding mathematical concepts of students. The study was conducted at Manba'ul Ulum Gayau Sakti Middle School with the research subject of grade VIII students in the academic year 2018/2019. The results showed that the researchers analyzed, designed a Student Worksheets with good and valid responses in accordance with the provisions of Badan Standar Nasional Pendidikan (BSNP) through the validation results from experts so that the Student Worksheets was feasible to be used in learning. In addition, the results of the study show that in terms of covers, contents, and results, it is effectively used. This can be seen from the study of the effect of Student Worksheets more effectively than not using problem-based Student Worksheets on understanding mathematical concepts of students.